Asymmetric vertical integration - Stefan Buehler; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2004)
We examine vertical backward integration in a reducedform model of successive oligopolies. Our key findings are: (i) There may be asymmetric equilibria where some firms integrate and others remain separated, even if firms are symmetric initially; (ii) Efficient firms are more likely to integrate vertically. As a result, integrated firms also tend to have a large market share. The driving force behind these findings are demand/mark-up complementarities in the product market. We also identify countervailing forces resulting from strong vertical foreclosure, upstream sales and endogenous acquisition costs.
Keywords: L13; L22; L40; L82; 330; successive oligopolies; vertical integration; efficiency; foreclosure; Vertikale Konzentration; Duopol; Theorie